Identification and characterization of a novel antimicrobial peptide compound produced by Bacillus megaterium strain isolated from oral microflora - Abdullah S.A. Al-Thubiani; Yahia A. Maher; Adel Fathi; Mohammed A.S. Abourehab; Mohammed Alarjah; Mohd S.A. Khan; Saleh B. Al- Ghamdi (Elsevier, 2018)
In recent years, the decreased efficacy of existing antibiotics toward management of emergent drug-resistant strains has necessitated the search for novel antibiotics from natural products. In this regard, Bacillus sp is well known for producing variety of secondary metabolites of potential use. Therefore, we performed an investigation to isolate and identify Bacillus sp from oral cavity for production of novel antimicrobial compounds. We extracted, purified, and identified a novel bioactive compound by B. megaterium (KC246043.1). The optimal production of compound was observed on de Man Rogosa and Sharpe broth by incubating at 37 °C, and pH 7.0 for 4 days. The bioactive compound was extracted by using n-butanol (2:1 v/v), purified on TLC plates with detection at Rf 7.8 cm; further characterized and identified as a cyclic ploypeptide sharing structural similarity with bacitracin. Minimum inhibitory concentration of bioactive compound was found to be 0.25, 0.5, 1.0, 3.125 and 6.25 μg/ml against Micrococcus luteus ATCC10240, Salmonella typhi ATCC19430, Escherichia coli ATCC35218. Pseudomonas aeruginosa ATCC27853 and Staphylococcus aureus ATCC25923 respectively, with no activity against Candida albicans ATCC10231. Our findings have revealed a novel cyclic peptide compound from B. megaterium with broad spectrum antimicrobial activity against both Gram positive and Gram negative bacteria. Keywords: Antibacterial, Bacillus megaterium, Bacitracin, Drug discovery, Peptide antibiotics